Directive Utterances In Holy Köran: A Pragmatics Perspective - Latifah, Latifah; , Dr. Maryadi, M. A.; , Agus Wijayanto, Ph.D (2016)
This research is aiming on 1) describing the sentence types of directive utterances used in English translation of Holy Köran Chapter An-Nisaa' and 2) describing the intentions of the illocution contained in directive utterances in English translation of Holy Köran Chapter An-Nisaa'. In this research, the researcher uses a descriptive qualitative as the type of the research. The object of the study is directive utterances contained in Holy Köran Chapter An-Nisaa'. The data of the study is English translation of Holy Köran Chapter An-Nisaa'. The researcher uses documentation to collect the data then coding the directive utterances contained in Holy Köran Chapter An-Nisaa'. The techniques of analyzing the data are describing the sentence types contained the directive utterances in Holy Köran Scripture on Chapter An-Nisaa' by refering to the theory of Yule (1996) based on the theory of classification of sentences by type of Frank (1972) and describing the illocution meaning of directive utterances in Holy Köran Scripture on Chapter An-Nisaa' verses 1-176 by referring to the theory of Levinson (1983) and describing the intention contained in the illocution meaning of directive utterances by referring to the theory of Kreidler (1996) which is based on the speech context by refering to the theory of Hymes (1972). The result of this study shows that 1) there are two sentence types of directive utterances used in Holy Koran Chapter An-Nisaa' namely: declarative sentence and imperative sentence. There are actually three sentence types of directive utterances based on theory Yule's theory. However the writer does not find interrogative sentences. The sentence type of declarative has 6 data (11, 32%) and imperative has 47 data (88, 67%). 2). There are three categories of intention of directive utterance used in Holy Koran Chapter An-Nisaa' namely: commanding, prohibiting, and ordering. There are actually five intentions of directive utterances based on the Kreidler's theory (1996). The intention of commanding has 27 data (50, 94%), prohibiting has 21 (39, 62%), and ordering has 5 data (9, 43%).